Potential Influence of Selenium, Copper, Zinc and Cadmium on L-Thyroxine Substitution in Patients with Hashimoto Thyroiditis and Hypothyroidism - Rasic-Milutinovic, Z.; Jovanovic, D.; Bogdanovic, G.; Trifunovic, J.; Mutic, J. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Background: Besides genetic factors, it is known that some trace elements, as Selenium, Copper, and Zinc are essential for thyroid gland fuction and thyroid hormone metabolism. Moreover, there were some metals effect that suggested patterns associated with overt thyroid disease.Aim of study: Hashimoto thyroiditis (HT), chronic autoimune inflamation of thyroid gland with cosequtive hipothyroidism, is common disease in Serbia, and we thought it is worthwile to explore potential effects of essential and toxic metals and metalloides on thyroid function and ability to restore euthyroid status of them.Results: This cross-sectional, case-control, study investigated the status of essential elements (Selenium,Copper,and Zinc) and toxic metals and metalloides (Al, Cr, Mn, Co, As, Cd, Sb, Ba, Be, Pb and Ni) from the blood of 22 female, patients with Hashimoto thyroiditis and overt hypothyroidism, and compared it with those of 55 female healthy persons. We tried to establish the presence of any correlation between previous mentioned elements and thyroid function in hypothyroid patients and healthy participants.Conclusions: The results of our study suggested that the blood concentration of essential trace elements, especially the ratio of Copper, and Selenium may influence directly thyroid function in patients with HT and overt hypothyroidism.Thus, our findings may have implication to life-long substitution therapy in terms of l-thyroxine dose reduction. Furthermore, for the first time, our study shown potential toxic effect of Cadmium on thyroid function in HT patients, which may implicate the dose of l-thyroxine substitution.
Keywords: thyrotropin; thyroiditis; thyroidy